MANAGEMENT OF LAMPUNG MUSEUM AS A TOURIST ASSET - Jarot Bayu; Ali Imron (FKIP UNIVERSITAS LAMPUNG, 2020)
ABSTRACTIn fact, currently in the Bandar Lampung area, there are many historical tourism assets that are served to attract tourists as foreign exchange earnings for the state and regional revenue (PAD) in Bandar Lampung itself. The existence of museum objects that are improving rapidly over time, the beauty of natural tourism and historical tourism adorn the existence of interesting museum tourist objects to visit. This study aims to find out in depth the management strategies carried out by the Lampung Museum to attract tourists to visit the museum so that the Lampung Museum is a tourist asset. The results obtained by researchers regarding the management of the Lampung Museum as a tourist asset, namely the Lampung Museum is a tourist asset because this museum holds many historical assets and items of Lampung that can continue to be seen over time. The Lampung Museum also keeps its appearance updated so that it can attract the public's interest in visiting the Museum. Collections at the Lampung Museum are also the most storing items related to the history of Lampung The Lampung Museum has a museum collection classified into 10 (ten) types of museum collections, has locations strategic in the middle of Lampung city and also a large building with typical Lampung architecture. The Lampung Province State Museum also has a fixed source of funding from the Lampung Regional Budget (APBD) every year. Keywords: Tourism Assets, Lampung Museum Doi: http://dx.doi.org/10.23960/pesagi.v8.i2.2020.02